Developing a Scientific-Based Instrument to Measure Wasathiyyah Values among Islamic University Students - Nugroho, Muhammad Aji; Billah, Arif; Zakaria, Abd Razak (Indonesian Journal of Islamic Education Studies (IJIES), 2025)
Wasathiyyah Islam is essential in shaping students’ character in Islamic higher education. However, standardized instruments do not assess students’ attitudes toward these values. This study aims to develop a valid and reliable instrument to measure wasathiyyah values among students at the Faculty of Islamic Education and Teaching (FTIK), UIN Salatiga. Using a Research and Development (R&D) design adapted from the Borg and Gall model, the study included item development, expert validation, field testing, and revision. The instrument was tested on 200 students from the Islamic Education and Science Education programs using a Likert scale. Data collection was conducted through surveys. Expert review confirmed content validity, and reliability testing using Cronbach’s Alpha produced a score of α = 0.89, indicating high internal consistency. The values measured: tawasuth (moderation), i’tidal (justice), tasamuh (tolerance), tawazun (balance), syura (deliberation), islah (reform), qudwah (exemplary leadership), muwathanah (citizenship), and musawwah (equality), were theoretically integrated into the instrument. Results showed high student agreement with the values, supporting the instrument’s effectiveness. This tool helps evaluate character education and can inform future research and curriculum development in Islamic higher education.